2021
DOI: 10.1002/cnr2.1468
|View full text |Cite
|
Sign up to set email alerts
|

The cost, survival, and quality‐of‐life implications of guideline‐discordant imaging for prostate cancer

Abstract: Background: National Comprehensive Cancer Network (NCCN) guidelines for incident prostate cancer staging imaging have been widely circulated and accepted as best practice since 1996. Despite these clear guidelines, wasteful and potentially harmful inappropriate imaging of men with prostate cancer remains prevalent.Aim: To understand changing population-level patterns of imaging among men with incident prostate cancer, we created a state-transition microsimulation model based on existing literature and incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In trauma patients, a 37‒47% cost reduction was shown, while the changes in cost were small in the overall use of imaging, as some examinations increased in use while others were reduced. Other studies on various patient groups showed 34‒70% cost reduction [ 59 , 94 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…In trauma patients, a 37‒47% cost reduction was shown, while the changes in cost were small in the overall use of imaging, as some examinations increased in use while others were reduced. Other studies on various patient groups showed 34‒70% cost reduction [ 59 , 94 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Schultz et al took into account the overall consumption of health services by the patients and reported lower enzalutamide costs due to less use of health services (outpatient, inpatient, and emergency) [ 38 , 39 ]. The important point is that most of these results were obtained by indirect comparisons of the mentioned drugs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complementarily, the work reflected in the article by Winn et al [ 23 ] created a simulation model to compare “appropriate imaging” with the status quo. According to the authors, applied imaging, radiation, and surgery had an associated cost of US$409, US$23,145 and US$28,507, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Winn et al [ 23 ] created a state-transition microsimulation model to understand changing population-level patterns of imaging among men with incidental prostate cancer. The results indicated that when only high-risk men were prioritized for imaging tests compared with the status quo (real-world practice from the SEER-Medicare database), both the population rate of imaging tests and average per-person expenditure on imaging tests declined.…”
Section: Discussionmentioning
confidence: 99%